Avaliação da associação entre nível sérico de sirtuína 2 e doença de Alzheimer - Dauar, Marina Tedeschi [UNIFESP] (2017)
Introduction: Alzheimer's disease (AD) is the most prevalent form of degenerative dementia and there is no effective treatment to prevent its progression. An important step in the search for a cure is the identification of a biomarker able to diagnose the disease early in the pathological process, at which point a pharmacological intervention would be effective. Sirtuins are proteins present in most living organisms and their functions have been related to the control of healthy longevity, neuroprotection and the pathophysiology of dementia. Sirtuin 1 is altered in the serum and plasma of AD patients representing a potential biomarker for the disease. It has already been showed that the T allele of the rs10410544 polymorphism of the Sirtuin 2 (SIRT2) gene is associated with a greater risk of development of AD, but the potential of SIRT2 as a biomarker of AD needs to be better investigated. Objective: To evaluate the association between serum SIRT2 and AD. Evaluate the impact of SIRT2 on risk factors of AD and the correlation of SIRT2 with clinical parameters of the disease. Methods: we conducted a case-control study, which included patients with AD and controls without cognitive deficit. Clinical information was obtained through medical consultation and clinical and neuropsychological tests. The serum level of SIRT2 was measured by the ELISA method, fasting glucose was measured by colorimetric assay and glycated hemoglobin by HPLC. Results: Thirty patients with AD and 14 subjects without cognitive deficit were included. No difference was found in the level of serum SIRT2 between AD and controls (p = 0.247). The logistic model that used SIRT2 levels to predict whether an individual would be in the case group or control group was not different than 50%. SIRT2 levels showed no difference according to the diagnosis of hypertension, hyperlipidemia, anxiety or depression. SIRT2 levels were not correlated with age, sex, length of evolution and severity of the disease or fasting glucose levels. We found that serum SIRT2 levels were significantly increased in patients with type 2 diabetes compared to non-diabetic patients (p=0.027). There was also a positive correlation between the levels of glycated hemoglobin and SIRT2 (p=0.027). Conclusion: No association was found between serum SIRT2 and AD. The findings suggest a role of SIRT2 on the pathophysiology of type 2 diabetes that deserves to be further investigated.